The Malawi National eHealth Strategy - Malawi Government: Ministry of Health (Malawi Government, 2021)
In order to strengthen the implementation of Health Management Information Systems (HMIS), the Ministry of Health completed the development of the Health Information Systems (HIS) Strategy in 2013. The aim of the strategy was to address HMIS weakness in support of the Health Sector Strategic Plan (HSSP). Recognizing that addressing these weaknesses in the information age required a comprehensive computerization process, the HIS strategy recommended, as one of its strategies, to have an eHealth Strategy developed. This eHealth Strategy is therefore a fulfillment of the HIS Strategy action item. The eHealth Strategy aims at building the foundations for ICT infrastructure, implementation of ehealth solutions, facilitating adoption of new ehealth solutions and enhancing governance in the implementation of this strategy. The strategy identifies national ehealth information standards, computing infrastructure, national connectivity services, identification and authentication, reliable power supply and information protection as foundations for ICT infrastructure. The ehealth solutions, which represent the tangible means to interact with the health system electronically, include national priority ehealth solutions, telehealthcare, individual electronic health records and continuous professional development using e-learning. The MoH is thankful to the team that developed the strategy. The team comprised representatives from Ministry of Health, I-TECH Malawi, Baobab Health Trust, Luke International Norway, the CDC and the eGovernment department. Special thanks to WHO which substantially financed the strategy development process, the CDC and I-TECH Malawi also for their financial support.